Can Internet penetration curb the spread of infectious diseases among regions?—Analysis based on spatial spillover perspective - Yu, Dongsheng; Li, Hui; Yu, Juanjuan (Frontiers in Public Health, 2023)
Based on the outbreak of COVID-19, this paper empirically studied the impact of Internet penetration on the incidence of class A and B infectious diseases among regions in spatial Dubin model, by using health panel data from 31 provinces in China from 2009-2018. The findings showed that: (1) the regional spillover effect of incidence of class A and B infectious diseases was significantly positive, and that is most obvious in the central regions; (2) Internet penetration not only has a positive effect on curbing the spread of infectious diseases within the local region but also help to inhibits the proximity spread of infectious diseases in neighborhood, showing the synergistic effect of "neighbor as a partner" in joint prevention and control mechanism.(3) The "digital gap" between regions, urban and rural areas, and user structures had led to significant group differences in the effect of the Internet on suppressing the spread of Class A and B infectious diseases. The findings of this paper provide a reference for understanding the potential role of the Internet in the COVID-19 and also provide policy support for the construction of Internet-based inter-regional "joint prevention and control mechanism" in public health events.